PENGARUH PENERAPAN PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) PADA PERUSAHAAN PEMBIAYAAN KOTA BENGKULU - Lidia Natalia; Isma Coryanata (Jurnal Akuntansi, 2018)
A fraud was an action to deceive other parties for personal advantages. This study aimed at investigating the influence of internal control, organizational commitment, and organizational culture on tendency of fraud. This study applied quantitative approach and data was collected by using questionnaires as instrument. This study was conducted at Finance’s Company of Bengkulu City. Samples were selected by applying purposive sampling technique. The samples of this study were the employees of finance departments of the 11 finance with respondents as many as 33 people. The technique of data analysis applied was multiple linear regression technique assisted by SPSS 23 for Windows program. The result of the analysis showed that (1) the internal control had negative and influence on fraud tendency, (2) the organizational commitment had negative and influence on fraud tendency, (3) the organizational culture had negative and influence on fraud tendencyKey words: internal control, commitment, culture, fraud.